Development and Implementation of an e-Learning Program on Glasgow Coma Scale - Xavier, Teenu; Kuriakose, Merin Lisa; Robin, Metilda; Agrawal, Deepak (Indian Journal of Neurotrauma, 2021)
Background With the advancement in technology, e-learning is an attractive platform to facilitate online continuing medical education. The aim of the study was to develop a web-based nursing education program on the Glasgow coma scale (GCS) and to assess the effectiveness of this module in improving the knowledge of nurses.Methods A one-group pretest posttest study was conducted among nurses working in a tertiary care hospital in New Delhi, India, from November 2015 till July 2016. Before administering the GCS module, an online questionnaire was used to assess the baseline knowledge. After the completion of the module, a posttest questionnaire was administered and assessed.Results A total of 3500 users completed the e-learning GCS module. The mean pretest score was 4.2 ± 2.1, and the mean posttest score was 7.3 ± 2.5. The mean difference in the score was statistically highly significant (p < 0.05).Conclusion The e-learning module is an effective means of providing continuing online education to the nurses, so that they can update their knowledge.
Keywords: e-learning; knowledge; glasgow coma scale; nurses; evaluation